Medical versus surgical termination of early pregnancy: satisfaction with care, emotional impact and acceptability of the procedure - Akkenapally, Prasanna L.; Kamineni, Vasundhara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim of the study was to compare the satisfaction with care and acceptability of the procedure next time between medical and surgical termination of pregnancy (TOP) and the factors affecting it. Methods: This is a prospective observational study conducted at Jyothi Maternity Centre, a project of population health services of India (PHSI). Total 213 women were included in the study, of these 108 women received medical termination of pregnancy (MTOP) and 105 received surgical termination of pregnancy (STOP). Questionnaires regarding satisfaction with care, experience of care, psychological rating scales and acceptability were given at the follow- up visit at two weeks. The data was collected and computed for statistical analysis. Results: Women in both the groups were similar with respect to age, marital status, socioeconomic status, educational status and parity. The mean age was 24 years. The success rate with STOP (100%) was more than MTOP (79.6%), with p -value of 0.001. The experience of care comparing the semantic variables showed MTOP to be less painful and safer, while STOP was good and faster. The total mean impact scores and depression scores of MTOP were higher than STOP and it was statistically significant with p- values of 0.010 and < 0.001 respectively. The acceptability rate with MTOP was 79.6% and with STOP 95.2%. Conclusions: Satisfaction with both the methods of medical and surgical abortion is high. Acceptability of the procedure next time was more with surgical abortion. MTOP had higher emotional impact.